2021
DOI: 10.1371/journal.pbio.3001070
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacteria-derived 5-hydroxyindole is a potent stimulant of intestinal motility via its action on L-type calcium channels

Abstract: Microbial conversion of dietary or drug substrates into small bioactive molecules represents a regulatory mechanism by which the gut microbiota alters intestinal physiology. Here, we show that a wide variety of gut bacteria can metabolize the dietary supplement and antidepressant 5-hydroxytryptophan (5-HTP) to 5-hydroxyindole (5-HI) via the tryptophanase (TnaA) enzyme. Oral administration of 5-HTP results in detection of 5-HI in fecal samples of healthy volunteers with interindividual variation. The production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 84 publications
0
30
0
Order By: Relevance
“…Other reports showed that colonization with gut microbiota increases gut motility in ex-GF animals in conjunction with an elevated luminal 5-HT level, while administration of pharmacologic antagonists of 5-HT 4 receptors resulted in recovery GI transit in GF rodents [ 105 , 124 , 138 ]. In addition, gut bacteria-derived 5-hydroxyindole, a major 5-HT metabolite, translocates through intestinal smooth muscle cells and directly accelerates colonic motility via the activation of L-type calcium channels [ 139 ]. Moreover, BTBR mice, a mouse model of ASD, showed an impaired serotonergic pathway with the downregulation of Tph1 and upregulation of Sert in the gut, which was associated with a reduction in 5-HT-producing Blautia bacteria [ 140 ].…”
Section: Microbiota-mediated Serotonergic Signaling In Ibs Pathologymentioning
confidence: 99%
“…Other reports showed that colonization with gut microbiota increases gut motility in ex-GF animals in conjunction with an elevated luminal 5-HT level, while administration of pharmacologic antagonists of 5-HT 4 receptors resulted in recovery GI transit in GF rodents [ 105 , 124 , 138 ]. In addition, gut bacteria-derived 5-hydroxyindole, a major 5-HT metabolite, translocates through intestinal smooth muscle cells and directly accelerates colonic motility via the activation of L-type calcium channels [ 139 ]. Moreover, BTBR mice, a mouse model of ASD, showed an impaired serotonergic pathway with the downregulation of Tph1 and upregulation of Sert in the gut, which was associated with a reduction in 5-HT-producing Blautia bacteria [ 140 ].…”
Section: Microbiota-mediated Serotonergic Signaling In Ibs Pathologymentioning
confidence: 99%
“…5-hydroxyindole has a marginal effect on the richness and composition of the cecal microbiota in wild-type Groningen rats Recently, we showed that a daily oral administration of the gut microbiota-produced 5-hydroxyindole (30 mg/kg) to wild-type Groningen (WTG) rats for 11 days results in a signi cant decrease of the total gut transit time (TGTT) [7].…”
Section: Resultsmentioning
confidence: 99%
“…Because the gut transit time was signi cantly affected in the 5-hydroxyindole-treated group [7], the TGTT was tested for its association with the abundance of genera using Spearman correlations. The correlation analysis revealed nine genera to be associated with the TGTT covariate (Spearman, P value < 0.05); Figure 1D; Table 2; Table D in Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations